Characterising clinical Staphylococcus aureus isolates from the sinuses of patients with chronic rhinosinusitis - Brett Wagner Mackenzie (Nature Portfolio, 2021)
Abstract The role of Staphylococcus aureus in the pathogenesis of the chronic sinonasal disease chronic rhinosinusitis (CRS), has not been definitively established. Comparative analyses of S. aureus isolates from CRS with those from control participants may offer insight into a possible pathogenic link between this organism and CRS. The intra- and inter-subject S. aureus strain-level diversity in the sinuses of patients with and without CRS were compared in this cross-sectional study. In total, 100 patients (CRS = 64, control = 36) were screened for S. aureus carriage. The overall carriage prevalence of S. aureus in this cohort was 24% (CRS n = 13, control n = 11). Cultured S. aureus isolates from 18 participants were strain-typed using spa gene sequencing. The bacterial community composition of the middle meatus was assessed using amplicon sequencing targeting the V3V4 hypervariable region of the bacterial 16S rRNA gene. S. aureus isolates cultured from patients were grown in co-culture with the commensal bacterium Dolosigranulum pigrum and characterised. All participants harboured a single S. aureus strain and no trend in disease-specific strain-level diversity was observed. Bacterial community analyses revealed a significant negative correlation in the relative abundances of S. aureus and D. pigrum sequences, suggesting an antagonistic interaction between these organisms. Co-cultivation experiments with these bacteria, however, did not confirm this interaction in vitro. We saw no significant associations of CRS disease with S. aureus strain types. The functional role that S. aureus occupies in CRS likely depends on other factors such as variations in gene expression and interactions with other members of the sinus bacterial community.